2017
DOI: 10.1097/nmd.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Valued Living and Its Relationship to Medication Adherence in Patients with Bipolar and Comorbid Substance Use Disorders

Abstract: Bipolar disorder with comorbid substance abuse is associated with high rates of treatment nonadherence. Adherence interventions developed to date have had mixed effects in this population. Valued living (i.e., the consistency between a patient’s personal values and daily actions) represents a potentially useful treatment target that may improve adherence. We investigated the relationship between valued living, medication adherence, symptoms, and functioning in a sample of 39 patients diagnosed with bipolar dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…EA-SGM people who can envision a healthy future in which they achieve their long-term goals have, on average, great psychological well-being [ 20 ], few risk behaviors [ 21 , 22 ], and improved use of health services [ 23 ]. These findings are consistent with the suicide prevention literature, in which goal-action consistency is targeted to reduce suicide risk [ 24 - 26 ] and improve mood regulation [ 27 , 28 ], and social connection is viewed as a factor that reduces the likelihood of developing suicidal ideation [ 29 , 30 ] or the intensity of suicidal ideation [ 31 ]. Studies are yet to evaluate the extent to which improving coping with discrimination, promoting positive affect, and improving social support are associated with reduced risk for suicide among EA-SGM groups.…”
Section: Introductionsupporting
confidence: 86%
“…EA-SGM people who can envision a healthy future in which they achieve their long-term goals have, on average, great psychological well-being [ 20 ], few risk behaviors [ 21 , 22 ], and improved use of health services [ 23 ]. These findings are consistent with the suicide prevention literature, in which goal-action consistency is targeted to reduce suicide risk [ 24 - 26 ] and improve mood regulation [ 27 , 28 ], and social connection is viewed as a factor that reduces the likelihood of developing suicidal ideation [ 29 , 30 ] or the intensity of suicidal ideation [ 31 ]. Studies are yet to evaluate the extent to which improving coping with discrimination, promoting positive affect, and improving social support are associated with reduced risk for suicide among EA-SGM groups.…”
Section: Introductionsupporting
confidence: 86%
“…Predictors were not extracted from studies which recruited participants with pre-specified combinations of diseases due to potential confounding associated with specific conditions, for example, a study of people living with bipolar disorder and depression assessing severity of depressive symptoms and psychological disability as predictors of non-adherence. 25 …”
Section: Methodsmentioning
confidence: 99%
“…The authors found significantly higher incidences of chronic fatigue syndrome, migraine, asthma, chronic bronchitis, multiple chemical sensitivities, hypertension, and gastric ulcers in BD patients. Chronic medical disorders were associated with more severe conditions, increased household and work maladjustment, and higher utilization of physical services in BD patients [2,28,29].…”
Section: Discussionmentioning
confidence: 94%